2016
DOI: 10.21930/rcta.vol17_num3_art:517
|View full text |Cite
|
Sign up to set email alerts
|

Estrategias de control de Moniliophthora roreri y Moniliophthora perniciosa en Theobroma cacao L.: revisión sistemática

Abstract: <p>Una de las limitaciones más importantes de la producción de cacao (Theobroma cacao L.) a nivel mundial es la presencia de enfermedades causadas principalmente por hongos fitopatógenos del género Moniliophthora sp., especialmente, Moniliophthora roreri y Moniliophthora perniciosa, causantes de las enfermedades moniliasis y escoba de bruja, respectivamente. Ambas enfermedades son altamente invasivas y endémicas del cacao. El objetivo de este estudio fue describir las estrategias de control implementadas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0
7

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(25 citation statements)
references
References 27 publications
0
13
0
7
Order By: Relevance
“…Thus, more environmentally friendly alternatives to control the development of phytopathogenic fungi are currently being proposed to reduce the potentially harmful effects of the continuous application of synthetic pesticides and fertilizers on agricultural lands [ 51 , 52 ]. These strategies involve the synergistic application of low doses of synthetic fungicides combined with biocontrol agents such as the nonpathogenic fungi Trichoderma, Clonostachys and Xylaria [ 13 , 14 ]. Recent studies under in vitro conditions have shown that when mancozeb is added to the culture medium in concentrations lower than 5 mg/mL, the mycelial growth of Trichoderma is not significantly inhibited [ 53 , 54 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Thus, more environmentally friendly alternatives to control the development of phytopathogenic fungi are currently being proposed to reduce the potentially harmful effects of the continuous application of synthetic pesticides and fertilizers on agricultural lands [ 51 , 52 ]. These strategies involve the synergistic application of low doses of synthetic fungicides combined with biocontrol agents such as the nonpathogenic fungi Trichoderma, Clonostachys and Xylaria [ 13 , 14 ]. Recent studies under in vitro conditions have shown that when mancozeb is added to the culture medium in concentrations lower than 5 mg/mL, the mycelial growth of Trichoderma is not significantly inhibited [ 53 , 54 ].…”
Section: Discussionmentioning
confidence: 99%
“…Thus, more environmentally friendly alternatives to control the growth of phytopathogens are currently being proposed. These strategies include the application of low doses of synthetic fungicides combined with the inoculation of biological agents such as nonpathogenic fungi ( Trichoderma, Clonostachys and Xylaria ) or bacteria ( Bacillus, Lysinibacillus and Solibacillus ) [ 13 , 14 ]. It has been documented that these microorganisms exhibit strong antagonistic interactions (i.e.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Estos árboles fueron recolectados en la Amazonía ecuatoriana, exclusivamente en las riberas de los ríos Tapiche y Tiputine. Aquellos árboles son los progenitores del INIAPT 526, INIAPT 527 e INIAPT 560, considerados genéticamente resistentes a la enfermedad, concordando con Tirado-Gallego et al (2016), quienes publican que el mejoramiento genético del árbol de cacao se vislumbra como una alternativa para enfrentar estos patógenos al conferir niveles crecientes de resistencia.…”
Section: Resistencia a Escoba De Brujaunclassified
“…La moniliasis es el principal problema fitosanitario y se caracteriza por la aparición de una mancha blanquecina, polvorienta que es altamente invasiva y endé-mica del cacao (Tuquerres, 2016;Tirado et al, 2016). Esta enfermedad causada por Moniliophthora roreri ha afectado a México desde 2005, y para Phillips-Mora, durante el 2013, las altas temperaturas afectaron el 70% de la producción.…”
unclassified